2006
DOI: 10.1002/asi.20367
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐version resources in digital libraries: Towards user‐centered displays

Abstract: Center's (OCLC) WorldCat. The goal of the study is to gauge the characteristics of bibliographic entities under study, to examine types of relationships these entities exhibit, and to collocate bibliographic entities according to the FRBR group 1 hierarchy of entities identified as works, expressions, manifestations, and items. The study's findings show that by assembling bibliographic records into interrelated clusters and displaying these according to the FRBR entity-relationship model, a new navigational ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…Improved search experience was early recognized as the key contribution of FRBR [2] and this has been the main motivation for research and experimental prototypes applying the model [8,11,3,6,20]. Unfortunately most systems developed so far are based on existing data, automatically transformed from MARC records into a FRBR-based representation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Improved search experience was early recognized as the key contribution of FRBR [2] and this has been the main motivation for research and experimental prototypes applying the model [8,11,3,6,20]. Unfortunately most systems developed so far are based on existing data, automatically transformed from MARC records into a FRBR-based representation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fattahi (), for example, talked of a superwork record as a meta‐record that would integrate all records presenting instances of a work as well as works about the work, thus generating a tool that would enable “better understanding, differentiating, relating, organizing and synthesizing information about bibliographic families” (Fattahi, , p. 6) by presenting the size of the bibliographic family, types of entities that are related to the work, as well as types of relationships that exist between works. Examples of how such data and relationships could be displayed were proposed by Ercegovac (), Yee (), and Carlyle (), who all mapped the data to hierarchical presentations. Carlyle (), for example, suggested a display scheme that presented “summary work displays” and “summary author displays,” each having a particular categorization and inner order based on the entities retrieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, usage of this model in real world applications tailored to the needs of real users has been less systematically explored, although some protoypes and studies can be found [4,2,7]. Model and vocabulary development as well as the creation of data sets is often driven by domain expert and needs to be complemented by best practice knowledge from application development and studying users.…”
Section: Introductionmentioning
confidence: 99%